Functional endoscopic sinus surgery (FESS) for the Management of Chronic rhinosinusitis (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To see the efficacy of surgery (FESS) and quality of life of the patient after Functional Endoscopic Sinus Surgery (FESS) for chronic rhinosinusiotis.Methods: It was a prospective type of study carried out Otolaryngology and Head-Neck Surgery Department of BIRDEM Hospital and Shaheed Suhrawardy Hospital, Dhaka from July 2009 to June 2010. Total 60 (sixty) patients were included in this study.Results: In this study, 22(36.67%) patients were operated for Ethmoidal polyp, 19(31.67%) for chronic rhinosinusitis, 9(15%) for Antrochoanal polyp, 6(10%) for Rhinosporidiosis and 4(6.67%) for Inverted papilloma. Per operative difficulties were gross DNS 07 (11.67%), unusual bleeding 6(10%), concha bullosa 5(8.33%). Post operative complications were periorbital echymoses (10%), Synechiae (1.67%), Epiphora (1.67%), infection(1.67%). Complete relief of symptoms were noted in 81.67% cases. Majority of patients 46(76.67%) were released from the hospital on 2nd post operative day.Conclusion: Instead of some limitations, outcome of functional endoscopic sinus surgery is rapidly flourishing, highly effective, less time consuming, less hospital stay & less expensive.Bangladesh J Otorhinolaryngol; October 2017; 23(2): 122-126